Jewish dealers and the European art market, c. 1860-1940 : negotiating cultural modernity - Davoli, Silvia; Davoli, Silvia; Stammers, Tom; Stammers, Tom (Contextualizing art markets, 2025)
"Adopting a far wider geography than any previous study, this is the first book to consider Jewish dealers as a coherent cohort, tied together by common contexts and strategies, but also a common vulnerability. The essays in this volume presents case studies from the mid-19th to mid-20th century across six thematic subsections: the historic art trade in Paris and London; the role of Jewish dealers as mediators between East and West; cosmopolitan dealers and modernist identities; Jewish art promoters and exhibition makers; the antisemitism faced by Jewish dealers; and the migration, circulation and reinvention of Jewish dealers in the 20th century"